Isoniazid Uptake in Relation to Growth Inhibition of Mycobacterium tuberculosis - Beggs, William H. (1968)
(14)C-isoniazid (INH) was used to study the relationship between drug uptake or binding by Mycobacterium tuberculosis and growth inhibition of the organism, which is dependent upon the concentration of drug and the duration of exposure. When strain H37R(a), grown in modified Sauton's liquid medium, was treated with 0.1 μg of INH per ml for 2 to 6 hr, followed by 10 μg of nicotinic hydrazide (NH) per ml to block further INH uptake, growth was retarded but not completely inhibited upon continued incubation. NH itself did not retard growth. However, cells treated in a similar manner with INH alone grew normally when diluted 1:100 in fresh, drug-free media. Uptake data showed that bacilli exposed to 0.1 μg of INH per ml accumulated 5.5, 9.7, and 12 mμg/mg of dry cells at 2, 4, and 6 hr, respectively. Other experiments suggested that once isoniazid is bound, it is not rapidly lost when NH is added or when the cells are diluted in fresh media. In the presence of 1.0 μg of INH per ml, tubercle bacilli took up 10 to 37 mμg/mg of dry cells in 20 to 90 min. These cells were not markedly inhibited when diluted 1:40 in fresh NH-containing media and incubated for 6 days. Growth inhibition of tubercle bacilli by INH depends on the uptake of sufficient drug, but the evidence obtained in this study suggests that the absolute concentration of bound INH is not as important in the action of the drug as is the maintenance of a critical cellular concentration for a requisite period of time.